Religiones omnívoras: el chamanismo chané y las relaciones interétnicas - Villar, Diego (Pontificia Universidad Católica del Perú. Fondo Editorial, 2007)
Of Arawak origin, the ethnic group identified as the Chané indigenous group in the Amerindian literature, settled on the eastern slopes of the Andes before the Conquest of the Occidental region or Paraguayan Chaco took place. There, this group engaged in complex inter-ethnic relationships with other Guarani-speaking ethnic groups, Chaco natives, and thereafter, as the colonization process consolidated, with several Creole social agents: landowners, foremen of sugar plantations, the military, and missionaries. Supported by ethnographic and ethno-historical documents, the author suggests that the open, flexible, malleable and integrating organization of Chané shamanism was marked by these multiple historical interactions, thereby becoming an ideal symbolic language to reflect the problems arising from situations of intercultural contact.

De origen arawak, el grupo étnico que la literatura amerindia llamó chané se estableció antes de la Conquista en El Chaco occidental, sobre las laderas orientales de los Andes. Allí trabó complejas relaciones interétnicas con otros grupos étnicos de habla guaraní, indígenas chaqueños y luego, en la medida en que se consolidó el proceso de colonización, también con diversos actores criollos: hacendados, patrones de ingenios, militares, misioneros. A través de documentación etnográfica y etnohistórica, se sugiere que el funcionamiento abierto, flexible, maleable e integrador del chamanismo chané lleva la marca de estas múltiples interacciones históricas, lo cual, por otra parte, lo transforma en un lenguaje simbólico ideal para problematizar las situaciones de contacto intercultural.
Omnivorous religions: Chané shamanism and inter-ethnic relationships
Keywords: Chamanismo; Relaciones interétnicas; Chané; Chiriguano; Gran Chaco; https://purl.org/pe-repo/ocde/ford#5.04.03